Korelasi Perubahan Kognitif Dengan Kejadian Depresi Pada Lansia - Shanti Rosmaharani; Pepin Nahariani; I’in Noviana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The elderly are a vulnerable group that has experienced many changes in function, two of them are cognitive and emotional changes. Cognitive changes in the elderly have a negative impact which is a separate stressor and become one of the factors that cause depression. The aims of study is to determine the correlation between cognitive changes and the level of depression in the elderly. Methods: The design of study used correlational analytic with cross sectional approach . The population in this study as many as 345 elderly. The sample in this study as many as 100 elderly. The sampling technique used in this study was simple random sampling technique. The questionnaire used for cognitive change was the Mini Mental Status Exam (MMSE) and the depression questionnaire was the Geriatric Depression Scale (GDS). statistical test used is spearman rank with 0.05.Results: The results of the statistical test p value 0.00 <0.05, which means that there is a correlation between cognitive changes and the level of depression in the elderly.Conclusion: The conclusion of this study is cognitive changes can be managed properly by the elderly and their families by using several recommended therapies so that they are not at risk of increasing the incidence of depression in the elderly.